2020
DOI: 10.1016/j.celrep.2020.107824
|View full text |Cite
|
Sign up to set email alerts
|

Zygotic Nuclear F-Actin Safeguards Embryonic Development

Abstract: Highlights d Filamentous actin is a hallmark of pronuclei in mouse zygotes d Polymerized nuclear actin is important for embryonic development d Zygotic nuclear F-actin is required for efficient DNA damage repair d The timely disassembly of nuclear F-actin is key to subsequent development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 66 publications
2
39
0
Order By: Relevance
“…One possible explanation for the gradual increase in the nuclear size is that nuclear swelling is mediated by a recently found player, nuclear actin ( Baarlink et al., 2017 ; Wei et al., 2020 ). We have shown that pronuclear volume is reduced when nuclear actin is depolymerized ( Okuno et al., 2020 ). Furthermore, in the cultured cells, nuclear swelling and chromatin decondensation after mitosis are mediated by nuclear actin assembly ( Baarlink et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the gradual increase in the nuclear size is that nuclear swelling is mediated by a recently found player, nuclear actin ( Baarlink et al., 2017 ; Wei et al., 2020 ). We have shown that pronuclear volume is reduced when nuclear actin is depolymerized ( Okuno et al., 2020 ). Furthermore, in the cultured cells, nuclear swelling and chromatin decondensation after mitosis are mediated by nuclear actin assembly ( Baarlink et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…[7,22,23] This includes light-regulatable nuclear protein export using the LEXY system to shuttle the small actin filament severing and disassembly factor Cofilin-1 in and out of the nucleus. [24,38] Here we applied the LEXY system to a relatively large protein and to an actin-regulated transcription factor MRTF-A. MRTF-A shuttles between cytoplasmic and nuclear compartment in an actin-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…This dual localization is required for maximal transcription; in fact, in the nucleus, actin regulates the activity of specific transcription factors, participates in several chromatin remodeling complexes, and associates with all three RNA polymerases [ 89 ]. Intriguingly, nuclear filamentous actin (F-actin) has been found after fertilization in zygote, inside the large and decondensed pronuclei [ 90 ]. It is required for fully functional pronuclei; in fact, its perturbation causes the mis-regulation of genes related to genome integrity, generating an abnormal development of mouse embryos [ 90 ].…”
Section: The Role Of the Linc Complex In Mechanotransductionmentioning
confidence: 99%
“…Intriguingly, nuclear filamentous actin (F-actin) has been found after fertilization in zygote, inside the large and decondensed pronuclei [ 90 ]. It is required for fully functional pronuclei; in fact, its perturbation causes the mis-regulation of genes related to genome integrity, generating an abnormal development of mouse embryos [ 90 ].…”
Section: The Role Of the Linc Complex In Mechanotransductionmentioning
confidence: 99%